Recycling of spent catalyst and waste sludge from industry to substitute raw materials in the preparation of Portland cement clinker - Kae-Long Lin; Kang-Wei Lo; Ming-Jui Hung; Ta-Wui Cheng; Yu-Min Chang (Sustainable Environment Research, 2017)
This study investigated the feasibility of using waste limestone sludge, waste stone sludge, iron oxide sludge, and spent catalyst as raw materials in the production of eco-cement. The compressive strength development of the Eco Cement-A (ECO-A) paste was similar to that of ordinary Portland cement (OPC) pastes. The compressive strength development of the ECO-B paste was higher than that of OPC pastes. In addition, the C2S (Ca2SiO4, C2S) and C3S (Ca3SiO5) minerals in the eco-cement paste were continuously utilized to hydrate the Ca(OH)2 and calcium silicate hydrates gel (Ca6Si3O12·H2O, C–S–H) throughout the curing time. When ECO-C clinker contained 8% spent catalyst, the C3S mineral content decreased and C3A (3 CaO·Al2O3) content increased, thereby causing the structure to weaken and compressive strength to decrease. The results showed that the developed eco-cement with 4% spent catalyst possessed compressive strength properties similar to those of OPC pastes.